Indonesian species of Dilatognathus Kluge 2012 (Ephemeroptera, Leptophlebiidae, Choroterpes s.l.) and species-specific sexual dimorphism in development of maxilla - Kluge, Nikita J. (Zootaxa, 2014)
Larvae, subimagoes and imagoes of both sexes reared from larvae of a new species Choroterpes (Dilatognathus) bogori sp.n. from Java are described. Formerly this species was described by Ulmer (1939) under the wrong name "Choroterpides exiguus (Eaton 1884)". In all species of Dilatognathus, maxilla of last instar larva has the same structure, but in Ch. (D.) cataractae its structure is different in previous instars, being different in males and females.